Special education needs activities for children with language difficulties: A comparative study in Belarusian and Norwegian preschools. Issue 2 (3rd April 2018) - Bahdanovich Hanssen, Natallia; Hansén, Sven-Erik
ABSTRACT: For the purposes of this study, we investigated how special educational needs activities were carried out in the available physical space for preschool children with language difficulties in Belarus and Norway. Muller's and Bernstein's concepts were used to recognise patterns of knowledge construction in special needs education. A qualitative comparative case study approach was used, and through video observations, four categories were identified that exposed various positions within the continuum of the following binary pairs: regulated – flexible; pre-defined – diffuse; consequential – casual; repetitive – disruptive . The preschools in both countries showed different profiles. The Belarusian preschools were oriented towards the first notion in the binary pairs, while the Norwegian preschools leaned towards the latter. The implications of the study's results deal with the question of preschool staff preparation, knowledge construction in special needs education, construction and content of curricular documents and the question of promoting a closer dialogue between different practices.